The Effectiveness of Psychoeducation to Reduce Anxiety and Insomnia among Patients with Chronic Kidney Failure in Hemodialysis Unit - Sumai, Shanty Amalia; Rahmat, Ibrahim; Warsini, Sri (Fakultas Ilmu-ilmu Kesehatan, 2023)
Patients with chronic kidney disease who undergo hemodialysis may feel anxiety and experience insomnia. Anxiety is one of the factors that affects insomnia in patients with chronic kidney disease. One of the nursing interventions to reduce patient anxiety and insomnia is psychoeducation. The purpose of this research was to determine the effect of psychoeducation to reduce anxiety and insomnia in patients with chronic kidney failure treated in the hemodialysis unit. This was a quasi-experimental research using pre-test and post-test design with control group. The total sample was 54 respondents using a convenience sampling technique. Insomnia was measured using the Insomnia Severity Index questionnaire and anxiety was measured using the Zung Self Rating Anxiety Scale questionnaire. Psychoeducation intervention was carried out within three weeks. The results showed there were differences of anxiety score in the intervention group (p<0.001) and control group (p=0.022). There were differences of insomnia score in the intervention group (p<0.001) and control group (p=0.029). The results of multivariate test showed that the factors significantly related to anxiety were age and comorbidity. Psychoeducation using booklets was effective to reduce anxiety and insomnia of patients with chronic kidney disease undergoing hemodialysis.